(untitled) - Brook-Hart, Guy (Cambridge, 2012)
Complete IELTS combines the very best in contemporary classroom practice with stimulating topics aimed at young adults wanting to study at university. The Student's Pack is ideal for self-study. It consists of the Student's Book with Answers with CD-ROM and the Audio CDs which contain all the material for the listening activities. The Student's Book with Answers contains 8 topic-based units with stimulating activities to ensure that students gain skills practice for each of the four papers of the IELTS exam. It also contains a complete IELTS practice test to allow students to familiarise themselves with the format of the exam. The CD-ROM contains additional skills, grammar, vocabulary and listening exercises.
Nghe - Nói B2.1,Ngữ pháp trung cấp
Keywords: English language,Tiếng Anh; Foreign speakers,Study and teaching,Nói tiếng nước ngoài,Dạy và học